Monoclinic superstructure in orthorhombic Ce10W22O81 from transmission electron microscopy. Issue 2 (17th March 2014) - Patout, Loïc; Jacob, Damien; Arab, Madjid; Pereira de Souza, Carlson; Leroux, Christine
<x xml:space="preserve">Abstract</x> A complex rare‐earth tungstate structure, present in a two‐phased powder, was solved by electron diffraction, precession and high‐resolution electron microscopy. The orthorhombic space group Pbnm and the atomic positions deduced from X‐ray diffraction experiments were confirmed for Ce10W22O81. A C2/c monoclinic superstructure, with cell parameters a = 7.8, b = 36.1, c = 22.2 Å and β = 100.2°, was shown and attributed to a partial oxidation of Ce3+ leading to interstitial oxygen ions.